2009
DOI: 10.1186/1471-2474-10-159
|View full text |Cite
|
Sign up to set email alerts
|

Increased hallux angle in children and its association with insufficient length of footwear: A community based cross-sectional study

Abstract: BackgroundWearing shoes of insufficient length during childhood has often been cited as leading to deformities of the foot, particularly to the development of hallux valgus disorders. Until now, these assumptions have not been confirmed through scientific research. This study aims to investigate whether this association can be statistically proven, and if children who wear shoes of insufficient length actually do have a higher risk of a more pronounced lateral deviation of the hallux.Methods858 pre-school chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
6
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 22 publications
4
85
6
7
Order By: Relevance
“…Most authors agree that both hallux valgus and other toe deformities are not genetic, but result from abnormal reactions with footwear [13][14][15]. The research by Klein et al [16] covering a group of 858 pre-school children from an Austrian province showed that only 23.9% of feet presented a straight position of the great toe. In addition, 808 children wore too small shoes and 812 had inadequate outdoor footwear.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors agree that both hallux valgus and other toe deformities are not genetic, but result from abnormal reactions with footwear [13][14][15]. The research by Klein et al [16] covering a group of 858 pre-school children from an Austrian province showed that only 23.9% of feet presented a straight position of the great toe. In addition, 808 children wore too small shoes and 812 had inadequate outdoor footwear.…”
Section: Discussionmentioning
confidence: 99%
“…vârful îngust ºi strâmt. La purtarea acestui tip de încãlþãminte, halucele este obligat sã se deplaseze în lateral, ceea ce ar putea contribui la deformarea de tip hallux valgus [1] ºi la o distribuþie anormalã a presiunii plantare. Întrucât purtarea acestui tip de încãlþãminte este nocivã pentru picioarele copiilor, studiile de evaluare sunt dificil de efectuat.…”
Section: Introductionunclassified
“…Cu privire la copiii sãnãtoºi, Klein ºi colab. [1] au mãsurat AoH la 800 de copii sãnãtoºi ºi au explorat corelaþia dintre lungimea interioarã a încãlþãmintei pentru copii ºi apariþia deformãrii de tip hallux valgus; în plus, Ferrari ºi colab. [10] au comparat distribuþia presiunii plantare la bãieþi ºi la fete pentru a explica de ce deformarea de tip hallux valgus se regãseºte de obicei la populaþia femininã.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…( Roddy et al, 2008) In children, Klein et al reported only 23.9% of children's feet with a straight position of the great toe; in all the rest, the position of the great toe varied between a hallux angle of 1 degree up to 19 degrees valgus position (14.2% with a valgus deviation of equal to or greater than 10 degrees). (Klein et al, 2009) A female preponderance of 2:1 was reported in a study of schoolchildren's feet (Wilkins, 1941); the ratio increases up to 3:1 in military recruits (Hewitt, 1953;Marwil & Brantingham, 1943), until to reach approximately the ratio of 15:1 in adult patients (Hardy & Clapham, 1951). Therefore, the prevalence in women increased as patient age increased, also probably due to the use of fashionable female shoes.…”
Section: Epidemiologymentioning
confidence: 99%